2005
DOI: 10.1029/2005ja011021
|View full text |Cite
|
Sign up to set email alerts
|

Stormtime coupling of the ring current, plasmasphere, and topside ionosphere: Electromagnetic and plasma disturbances

Abstract: [1] We compare plasma and field disturbances observed in the ring current/plasmasphere overlap region and in the conjugate ionosphere during the magnetic storm of 5 June 1991. Data come from the Combined Release and Radiation Effects Satellite (CRRES) flying in a geostationary transfer orbit and three satellites of the Defense Meteorological Satellite Program (DMSP) series in Sun-synchronous polar orbits. In the region between ring current nose structures and the electron plasma sheet, CRRES detected wave-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 75 publications
9
134
0
Order By: Relevance
“…showed that they were directly linked to the partial ring current localized pressure peak, and other observations and numerical modeling has confirmed and further quantified this relationship (e.g. Garner et al 2004;Mishin and Burke 2005;Yu et al 2015;Yuan et al 2016;Califf et al 2016). SAPS are relatively stable during storms, being a persistent feature across the evening sector that can last for many hours (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 76%
“…showed that they were directly linked to the partial ring current localized pressure peak, and other observations and numerical modeling has confirmed and further quantified this relationship (e.g. Garner et al 2004;Mishin and Burke 2005;Yu et al 2015;Yuan et al 2016;Califf et al 2016). SAPS are relatively stable during storms, being a persistent feature across the evening sector that can last for many hours (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 76%
“…The upward ion flow could be explained as a consequence of temperature gradients induced by frictional heating of ions at lower altitudes, from where, unfortunately, observational data are not available. It is generally accepted that high electron temperatures in the topside ionosphere are the result of downward transport of heat generated inside the inner magnetosphere due to Coulomb collisions between ring current ions and plasmaspheric particles (Mishin and Burke, 2005;Wang et al, 2006). According to Wang et al (2006) and Prölss (2006) the equatorward edge of the electron temperature gradient indicates the location of the equatorward edge of the ring current.…”
Section: Modeled Convection Patterns Based On Imf Valuesmentioning
confidence: 99%
“…The Earth's magnetic field should be slightly disturbed in the inner magnetosphere during this moderate storm [Tsyganenko et al, 2003]. We take into account the large-scale convection electric field in this study but ignore the substorm-associated field [e.g., Ganushkina et al, 2005;Goldstein et al, 2005;Mishin and Mishin, 2007;Mishin and Burke, 2005]. An effect of this substorm-associated impulsive electric field in the plasma energization, transport, and wave generation will be considered separately in the future publications.…”
Section: Approaches Used In Simulationsmentioning
confidence: 99%